Diagnostic features in 10 naturally occurring cases of acute fatal canine leptospirosis. (November 2014) - Rissi, Daniel R.; Brown, Cathy A.
The current report describes the diagnostic features in 10 cases of acute fatal canine leptospirosis with minimal renal and hepatic changes that may present a diagnostic challenge for the pathologist. Most affected dogs were less than 6 months of age and had a biochemical profile consistent with hepatorenal dysfunction. Clinical signs consisted of vomiting, depression, icterus, dehydration, diarrhea, and anorexia. All dogs died or were humanely euthanized within 3–7 days after the onset of clinical disease. Necropsy findings included pulmonary edema with hemorrhages, icterus, renal and hepatic pallor and swelling, and gastric edema with hemorrhage. Despite severe azotemia, histological changes in the kidneys were subtle in all dogs, and included mild renal tubular simplification, with single-cell necrosis and attenuation, along with minimal interstitial lymphoplasmacytic inflammation, edema, and hemorrhage. Hepatic lesions included scattered hepatocellular single-cell necrosis and hepatocellular dissociation. Prominent extrarenal lesions typically associated with uremia including vascular fibrinoid necrosis in multiple organs, pulmonary mineralization with occasional fibrinosuppurative exudation, and gastric mineralization were also present. Postmortem diagnostic confirmation was based on the detection of leptospiral antigen on fresh renal samples by fluorescent antibody test and on the demonstration of intact spirochetes in sections of kidneys using immunohistochemical staining. Acute fatal canine leptospirosis occurred as a fulminant hepatorenal disease affecting mainly young dogs, and the diagnosis was dependent on the recognition of the subtle renal changes with confirmation via fluorescent antibody testing or immunohistochemical staining.